Symbolic Meaning of Traditional of Tumbang Apam, Malay Community, Suhaid Village, Suhaid Sub-district, Kapuas Hulu District - Azizan, Muhammad; Chalimi, Ika Rahmatika; Rustiyarso, Rustiyarso (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research aims to  analyze  the symbolic meaning of the Tumbang Apam Traditional Tradition of the Malay Tribe of Suhaid Village, Suhaid District, Kapuas Hulu Regency. The type of research used  qualitative with an ethnographic approach. Data collection  used  bservation, interviews and documentation. The stages of data analysis include data collection, data reduction, data presentation and verification/concluding. The research results show that (1) The process of implementing the Tumbang Apam  Traditional Tradition starts from the preparation stage, implementation, to the closing stage. (2) The symbolic  meaning contained in each stage in the Tumbang Apam Traditional Tradition starting from the preparation stage such as selecting the place, calling, making the Apam cake to making Tumbang Apam, the implementation stage namely plain flour and Penumbangan Apam, the closing stage is reading prayers and eating together. (3) In its preservation, the Tumbang Apam Traditional Tradition has been passed down from generation to generation by traditional leaders in Suhaid Village, Suhaid District who also collaborate with the community there so that the Tumbang Apam Traditional Tradition in Suhaid Village, Suhaid District is still being carried out to this day.